INTERCORELATION OF TURBIDTY WITH PRIMARY PRODUCTIVITY AND NUTRIENT IN THE WATER EAST SUNGAITOHOR OF SUB-DISTRICT OF EAST TEBINGTINGGI, DISTRICT OF KEPULAUAN MERANTI, PROVINCE OF RIAU - Saul Heryanto H.N; Joko Samiaji; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The objective of the research is to find out water quality condition in most coastal water in East Sungaitohor especially turbidity and its effect toward water primary productivity and its nutrient. This research has been conducted in Sungaitohor waters, district of Kepulauan Meranti. The methods used is purposive sampling. Sampling has been conducted on March 4th, 2017 and nitrate, phospate analysis and turbidity conducted in Marine Chemistry Laboratory and phytoplankton identification has been conducted in Marine Biology in March 10th, 2017. The result shows that the range of turbidity in the waters around 32,07-190 NTU, nitrate consentration is about 2,325-2,4291 mg/L and phospate consentration around -0,5 – 5 mgC/m2/day. Corelation between turbidity and primary productivity, phitoplankton, nitrate, and phospate respectively shows very weak, moderate, moderate, and weak.Keywords: Turbidity, Primary Productivity, Nutrient, Phytoplankton